2022
DOI: 10.5194/jsss-11-41-2022
|View full text |Cite
|
Sign up to set email alerts
|

Method and experimental investigation of surface heat dissipation measurement using 3D thermography

Abstract: Abstract. Three-dimensional thermography describes the fusion of geometry- and temperature-related sensor data. In the resulting 3D thermogram, thermal and spatial information of the measured object is available in one single model. Besides the simplified visualization of measurement results, the question arises how the additional data can be used to get further information. In this work, the Supplement information is used to calculate the surface heat dissipation caused by thermal radiation and natural convec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The results showed that the size of these surface units has decreased by a factor of 2 to 3. This suggests that the point clouds obtained with the new system are more useful for post-applications, such as creating meshes for calculating the surface heat dissipation and computing the measured temperature values, as presented in Schmoll et al (2022). This will be assessed in a future work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the size of these surface units has decreased by a factor of 2 to 3. This suggests that the point clouds obtained with the new system are more useful for post-applications, such as creating meshes for calculating the surface heat dissipation and computing the measured temperature values, as presented in Schmoll et al (2022). This will be assessed in a future work.…”
Section: Discussionmentioning
confidence: 99%
“…For the geometric calibration, the calibration toolbox presented in Schramm et al (2021b) and the coded target presented in Schramm et al (2021a) were utilized. The codes can be downloaded from the following git repositories: https://doi.org/10.5281/zenodo.11367429 (Schramm et al, 2024) and https://doi.org/10.5281/zenodo.4596313 (Schramm and Ebert, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schramm et al [ 22 ] presented 3D thermograms and some advantages compared to other existing systems. Schmoll et al [ 23 ] also presented 3D thermography describing the fusion of geometry and temperature sensors, but for heat dissipation applications.…”
Section: Introductionmentioning
confidence: 99%